Measures to mitigate over-frequencies at Songo Rectifier Station - Fanequiço, Leonel José (My University, 2022)
Songo Rectifier Station is located 6 km away from the Cahora Bassa hydroelectric power station. It was designed to transmit 1920 MW from the 2075 MW generated to Apollo Inverter Station in South Africa. Frequency fluctuation at Songo is very high because the active power balance is easily destroyed after an HVDC disturbance. The three HVAC transmission lines plus two HVDC transmission lines of 1400 km each and 16 converter bridges in both stations (Songo and Apollo) make Songo Rectifier Station AC Busbar (BB-I) susceptible to events leading to over-frequencies. Furthermore, the generating units and converter bridges operate most of the time in full load conditions. Frequency fluctuation has a negative impact in the interconnected system. It causes the tripping of the sharply tuned AC harmonic filters and consequent tripping of the Bus Coupler (BC) at Songo, resulting in power reduction to Eskom or to ZESA. It may also cause the tripping of the 380 V AC converter valve cooling pumps due to overload and subsequent tripping of the entire Songo Rectifier Station. Therefore, the aim of this particular investigation is to propose mitigating measures to prevent over-frequencies at Songo Rectifier Station. The evaluation of the actual dynamic performance of the Grid Master Power Controller (GMPC); the evaluation of the actual dynamic performance of the HVDC controls; the reasons for tripping the AC filters during over-frequency events; and the interaction between the GMPC, HVDC controls and generator exciters for preventing over-voltages are the objectives of this particular investigation. To achieve these objectives both detailed models of the Cahora Bassa synchronous generators and Songo-Apollo HVDC transmission scheme were used for simulations on the PSCAD Version 5.0 software platform. Data recorded in the last 10 years by the Transient Fault Recorder (TFR), installed at Songo, was used for the investigation, especially to evaluate the dynamic performance of the GMPC and HVDC controls. The conclusions and mitigating measures proposed can be extended to other HVDC schemes and may also pave the way to further research on frequency fluctuation at hydroelectric power stations.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and Built Environment, School of Electrical and Information Engineering, University of the Witwatersrand, Johannesburg, 2022